Establishing space activities in non-space faring nations: An example of university-based strategic planning. (July 2018) - Faure, Pauline; Cho, Mengu; Maeda, George
Abstract: In 2015, Kyushu Institute of Technology initiated the Joint Global Multi-Nation Birds Satellite (BIRDS) program. As of September 2017, young professionals from Bangladesh, Ghana, Nigeria, Thailand, Mongolia, Philippines, Malaysia, and Bhutan are being involved in BIRDS program. To help the young professionals acquiring the right tools and preparing them to successfully establish indigenous space activities, the space strategic planning project was established in February 2017. During the project, young professionals from Bangladesh, Ghana, Mongolia, and Bhutan were invited to think about the strategy their home country should be following in the next ten years to achieve their country's goals in terms of space sciences, engineering, and utilization, while respecting the country needs and constraints. In this paper, the efforts undertaken by the different young professionals are reported and the guidelines for each country space strategic planning are described. From this work, the authors aim at promoting space activities development in non-space faring nations and encouraging non-space faring nations to find their right strategy to achieve sustainable indigenous space activities despite the nation's constraints. Highlights: Space strategic planning project dedicated to non-space faring nations' engineers. Necessity of tackling and broadening knowledge in multi-disciplinary space fields. Bangladesh, Ghana, Bhutan, and Mongolia drafted national space plan roadmap. Need of parallel capacity and infrastructure development to sustain space activities. Importance of combining practical and real cases with theoretical teaching.